Recurrent chronic suppurative osteomyelitis of the mandible - Rajkumar G; Hemalatha M; Shashikala R; Kumar D (Wolters Kluwer Medknow Publications, 2010)
Osteomyelitis of the maxillofacial skeleton is a rare condition in recent times. The combination of antibiotic therapy and surgical debridement is effective in the treatment of chronic suppurative osteomyelitis (CSO). This case report describes the successful surgical treatment of CSO of the mandible in an 18-year-old adult. Treatment included a pre-surgical course of antibiotics followed by sequestrectomy, resection of the coronoid process and removal of the pathologically fractured condylar process of the left side of the mandible. On post-operative clinical review at 1 week, the extra oral draining sinus healed with improved mouth opening.